Peran Manajerial Kepala Madrasah dalam Meningkatakan Kualitas Guru dan Siswa di Madrasah Aliyah Raudhatul Ulum Meranti - Liawati, Liawati; Firayanti, Yuni; Marhamah, Marhamah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to describe the managerial role of the madrasah principal in improving the quality of teachers and students at Madrasah Aliyah Raudhatul Ulum Meranti. The focus of this study is the madrasah principal's efforts to carry out his managerial functions to encourage improvements in the quality of education. The approach used is qualitative, using data collection techniques such as interviews, observation, and documentation. The results show that the madrasah principal has carried out his managerial role at the madrasah. To improve teacher quality, the madrasah principal held training in the creation of teaching modules, opened a discussion space, and provided motivation that has an impact on improving teacher competence and professionalism. In addition, to improve student quality, the madrasah principal created interest classes for students to pursue their respective fields.